REVIEW OF DIFFERENT RELEASES OF CRYPTOOL PACKAGE AS TOOL FOR INFORMATION RESOURCES SECURITY - Nataliia O. Zagatska (Інформаційні технології і засоби навчання, 2012)
The article describes the characteristic features of free software for information resources security CrypTool that combines effective realization of known encryption algorithms and their visual presentation. The considerable attention is given to using such software in the course of Cryptology training that allows considering a wide range of questions for information resources security. Conducted a detailed review and comparative analysis of all available releases of the software among them allocated the most effective concerning realization of encryption algorithms and convenience interface.